Human HSP 60 peptide responsive T cell lines are similarly present in both Behcet's disease patients and healthy controls - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Heat shock protein (HSP, 60/65 kDa) is investigated as a candidate autoantigen in Behcet's disease (BD), a systemic vasculitis of unknown origin, and a prominent response to 'disease-specific epitopes' of mycobacterial and human HSP60/65 is described in BD patients. In this study, long-term T cell lines from peripheral blood of BD patients (n = 6) and controls (n = 7) were stimulated with mycobacterial recombinant HSP and purified protein derivate (PPD) and expanded with IL-2. In the BD group, 15 out 27 and in the controls, 25 out of 35 PPD specific T cell lines have responded to the synthetic peptides of the human HSP60. Out of the primarily HSP-specific T cell lines, 17/23 in patients and 8/8 in controls did recognize a peptide of human origin. T cell lines specifically reactive to 136-150, 179-197, 244-258 and 336-351 could be raised with similar frequency in both groups. In contrast to a previous report, T cells also reacted to peptide 425-441 frequently in both groups. The results demonstrate that the human proliferative response to mycobacterial HSP may also target the self-protein in both BID patients and controls. However, the responsive T cells may have different effects depending on their functional features such as cytokine secretions. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: Behcet's disease; heat shock protein; HSP60; T cell line; HEAT-SHOCK-PROTEIN; MYCOBACTERIAL 65-KDA; IMMUNE-RESPONSE; RECOGNITION; RECEPTOR; EPITOPES; FLUID; BD